Toward Behavioral Web Services Using Policies - Maamar, Z.; Benslimane, D.; Mostefaoui, G.K.; Subramanian, S.; Mahmoud, Q.H. (IEEE transactions on systems, man and cybernetics. Part A, Systems and humans, 2008)
Making Web services context-aware is a challenge. This is like making Web service expose appropriate behaviors in response to changes detected in the environment. Context awareness requires a review and extension of the current execution model of Web services. This paper discusses the seamless combination of context and policy to manage behaviors that Web services expose during composition and in response to changes in the environment. For this purpose, a four-layer approach is devised. These layers are denoted by policy, user, Web service, and resource. In this approach, behavior management and binding are subject to executing policies of types permission, obligation, restriction, and dispensation. A prototype that illustrates how context and policy are woven into Web services composition scenarios is presented as well.